1993
DOI: 10.1111/j.1751-1097.1993.tb04904.x
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Improvements in Viral Inactivation With Brominated Psoralens, Naphthalenes and Anthracenes

Abstract: Amino or polyamino derivatives of naphthalene (N-H), anthracene (A-H) and 8-alkoxypsoralen (PSR-H) were prepared along with their monobrominated analogs (N-Br, A-Br and PSR-Br). The ammonium salts of these compounds are all water soluble and bind strongly to calf thymus DNA and to lambda phage, a double-helical DNA, protein-coated virus. Binding of the sensitizer to DNA occurs, presumably by a mixture of hydrophobic, intercalative and electrostatic interactions. Relative binding constants to calf thymus DNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Recently, several groups have reported the synthesis of novel psoralens with greatly enhanced pathogen inactivation activity and reduced mutagenicity. Rai, Yerram and colleagues have reported the synthesis of brominated psoralens (PSR-Br) which appear to have improved activity compared to AMT and 8-MOP [38,39]. However, most of these studies have been carried out with non-pathogenic viral targets and require confirmation with cell-free and cell-associated targets.…”
Section: Decontamination Of Platelet Concentratesmentioning
confidence: 99%
“…Recently, several groups have reported the synthesis of novel psoralens with greatly enhanced pathogen inactivation activity and reduced mutagenicity. Rai, Yerram and colleagues have reported the synthesis of brominated psoralens (PSR-Br) which appear to have improved activity compared to AMT and 8-MOP [38,39]. However, most of these studies have been carried out with non-pathogenic viral targets and require confirmation with cell-free and cell-associated targets.…”
Section: Decontamination Of Platelet Concentratesmentioning
confidence: 99%
“…Recent work from our laboratory (24,25) and from other groups (26)(27)(28)(29)(30)(31) has investigated the potential role of electron transfer chemistry, and in particular radical cations, in psoralen photochemistry. We have demonstrated that the 8deoxyguanosine; GMP, guanosine 5Ј-monophosphate; HPLC, high-performance liquid chromatography; LC/MS, liquid chromatography/mass spectrometry; 7-MC, 7-methoxycoumarin; 8-MOP, 8-methoxypsoralen; PUVA, psoralen plus UVA irradiation; SCE, saturated calomel electrode; TMP, thymidine 5Ј-monophosphate; 4,5Ј,8-TMP, 4,5Ј,8-trimethylpsoralen.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research efforts have been directed toward identifying the excited-state intermediates involved in the photocycloaddition chemistry of psoralens that are used in PUVA. Early attention focused on characterization of the triplet states of 8-MOP and other psoralens by transient absorption spectroscopy 8 and the measurement of singlet oxygen yields. A number of coumarin photosensitizers have also attracted attention since they do not form diadducts and can serve as models for the initial furan monoadduct that is the precursor to DNA cross-links. More recently, the importance of binding to proteins, cycloaddition reactions with unsaturated fatty acids, , and electron-transfer reactions , in psoralen photochemistry has been examined. A detailed understanding of the molecular basis for both the therapeutic and harmful effects of PUVA therapy is obviously required to aid in the further development of potential new therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] A number of coumarin photosensitizers have also attracted attention since they do not form diadducts and can serve as models for the initial furan monoadduct that is the precursor to DNA cross-links. [17][18][19] More recently, the importance of binding to proteins, 20 cyclo-addition reactions with unsaturated fatty acids, 21,22 and electrontransfer reactions 19,[23][24][25][26][27] in psoralen photochemistry has been examined. A detailed understanding of the molecular basis for both the therapeutic and harmful effects of PUVA therapy is obviously required to aid in the further development of potential new therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%